The Significance of Socio-Economic Status, Financial Sophistication, Salience and the Scale of Deliberation in UK Retirement Planning. - Clark, G; Knox-Hayes, J; Strauss, K (School of Geography and Environment (University of Oxford), 2008)
Many British workers rely upon their accumulated pension savings for retirement income. Whether they appreciate the importance of saving for the future, and whether they intend to do so, are not well-understood. Based upon a representative sample of UK residents, we show that the perceived importance of pension planning is positively correlated with respondents' risk tolerance, age and income, and whether their spouses participate in employer-sponsored pension plans. Those less likely to believe planning for the future is important are younger, earn less, are women, and will rely upon others for their expected retirement welfare. It is also apparent that generic sources of information provided remotely or at the national scale for individual and household pension planning, preparedness, and knowledge of annuities do not stand comparison with the perceived value of intimate and specialist relationships. The unit of retirement planning is typically the household, rarely the region, and hardly ever the nation. To better understand these findings we frame their interpretation with reference to recent behavioral research that emphasizes people's limited cognitive and social resources and the use of heuristics such as salience in setting priorities. The implications of this framework and our empirical findings for the design and delivery of private pensions conclude the paper.